Low sensitivity of rapid tests detecting anti-CoV-2 IgG and IgM in health care workers’ serum for COVID-19 screening - Larese Filon, Francesca; Purpuri, Antonio; Camata, Davide; Bovenzi, Massimo; Rui, Francesca; Ronchese, Federico; De Michieli, Paola; Marcello, Alessandro; Poggianella, Monica; Confalonieri, Marco; Salton, Francesco; Confalonieri, Paola; et al. (La Medicina del Lavoro, 2021)
Background: the sensitivity and specificity of a rapid antibody test were investigated for the screening of healthcare workers. Methods: the serum of 389 health care workers exposed to COVID-19 patients or with symptoms, were analysed. All workers underwent monthly the screening for SARS-CoV-2 with detection of viral RNA in nasopharyngeal swabs by RT-PCR. IgG antibody detection in serum was performed by Chemiluminescence Immunoassay (CLIA) and by the Rapid test (KHB diagnostic kit for SARS CoV-2 IgM/IgG antibody after a median of 7.6 weeks (25°-75° percentiles 6.6-11.5). Results: the rapid test resulted positive in 31/132 (23.5%), 16/135 (11.8%) and 0/122 cases in COVID-19 positive individuals, in those with only SARS-CoV-2 IgG antibodies and in those negative for both tests, respectively. Sensitivity was 17.6% (CI95% 13.2-22.7) and 23.5% (CI95% 16.5-31.6), and specificity was 100% (CI95% 97-100) and 100% (CI95% 97-100) considering Rapid test vs CLIA IgG or Rapid test vs SARS-CoV-2 positive RNA detection, respectively. Conclusion: the KHB Rapid test is not suitable for the screening of workers with previous COVID-19 infection.